2017
DOI: 10.1177/0885328217720812
|View full text |Cite
|
Sign up to set email alerts
|

Towards modular bone tissue engineering using Ti–Co-doped phosphate glass microspheres: cytocompatibility and dynamic culture studies

Abstract: The production of large quantities of functional vascularized bone tissue ex vivo still represent an unmet clinical challenge. Microcarriers offer a potential solution to scalable manufacture of bone tissue due to their high surface area-to-volume ratio and the capacity to be assembled using a modular approach. Microcarriers made of phosphate bioactive glass doped with titanium dioxide have been previously shown to enhance proliferation of osteoblast progenitors and maturation towards functional osteoblasts. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
(108 reference statements)
0
15
0
Order By: Relevance
“…In a previous study, we characterised the release of Co 2+ ions from CoO 0% and CoO 2% microspheres over a period of 21 days. 35 Although CoO concentrations used in this study were lower than those recognised to cause cytotoxic effects on human osteoblastic cells 15,42 and mesenchymal stem cells, 16 these results suggest that the soluble divalent Co 2+ ions may still interfere with Ca 2+ and Ti 4+ signalling that usually (as in the case of CoO 0% microspheres) leads to molecular events, such as increased expression of osteogenic transcription factors and subsequent osteogenic protein. 14,43,44 The observed lack of osteogenic induction on CoO 2% PG microspheres was expected to be somewhat compensated by clear improvements in vascular responses, an important consideration for creating 3D tissues that will require perfusion.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In a previous study, we characterised the release of Co 2+ ions from CoO 0% and CoO 2% microspheres over a period of 21 days. 35 Although CoO concentrations used in this study were lower than those recognised to cause cytotoxic effects on human osteoblastic cells 15,42 and mesenchymal stem cells, 16 these results suggest that the soluble divalent Co 2+ ions may still interfere with Ca 2+ and Ti 4+ signalling that usually (as in the case of CoO 0% microspheres) leads to molecular events, such as increased expression of osteogenic transcription factors and subsequent osteogenic protein. 14,43,44 The observed lack of osteogenic induction on CoO 2% PG microspheres was expected to be somewhat compensated by clear improvements in vascular responses, an important consideration for creating 3D tissues that will require perfusion.…”
Section: Discussionmentioning
confidence: 66%
“…Material characterisation as well as degradation and ions release studies for the microspheres have been previously published by our group. 35…”
Section: Glass Preparation and Microspheres Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental protocols are described in detail in Peticone et al 41 and De Silva Thompson et al, 42 and briefly overviewed here.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study by Guedes et al 16 found that 5 and 7 mol% TiO 2 conferred a stable degradation rate of the phosphate carriers, which motivated the use of these particular concentrations. Two non-cytotoxic CoO concentrations were also examined: 2 and 5 mol%, 41 as CoO has been found to encourage in vitro angiogenesis. Spherical phosphate glass microcarriers were manufactured following the procedure set out in Guedes et al 16 and sieved down to spheres with diameters between 63 and 106 μm.…”
Section: Methodsmentioning
confidence: 99%